Canada : what it is, what it can be - Martin, Roger L. (University of Toronto Press, 2012)
Written in an accessible style that helps general readers understand complex economic concepts, Canada: What It Is, What It Can Be exposes the myths currently guiding our public policy, and provides ground-breaking new approaches for realizing our full prosperity potential.
Keywords: Labor productivity -- Canada.; Competition -- Canada.; Economic development -- Canada.; Economic forecasting -- Canada.; Canada -- Economic policy.; Productivité -- Canada.; Développement économique -- Canada.; Prévision économique -- Canada.; BUSINESS & ECONOMICS -- General.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Competition; Economic development; Economic forecasting; Economic policy; Labor productivity; Canada; Volkswirtschaft.; Wirtschaftswachstum.; Wettbewerb.; Innovation.; Produktivität.; Wirtschaftspolitik.; Kanada.; Electronic books.